2022
DOI: 10.7759/cureus.25644
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Maxillary Sinus Squamous Cell Carcinoma at a Dedicated Cancer Institute: A Retrospective Study

Abstract: Introduction Squamous cell carcinoma arising at the maxillary sinus is a rare neoplasm, characterized by an aggressive growth pattern and glooming prognosis. The proximity of the maxillary sinus with complex anatomical structures such as the eye, skull base, infratemporal fossa, pterygomaxillary fossa, nasal cavities, and ethmoid sinuses makes the surgical treatment of tumors infiltrating into these structures very challenging. The study's objective was to investigate the prognostic factors of survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…21 Keerio et al compared modalities for maxillary SCC, finding adjuvant and neoadjuvant multimodal therapy yielded better outcomes. 22 Kuo et al showed improved survival with induction chemotherapy over adjuvant chemotherapy. 23 The heterogenous results of these studies underscore the need for future prospective trials on the efficacy of various treatment regimens for sinonasal malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Keerio et al compared modalities for maxillary SCC, finding adjuvant and neoadjuvant multimodal therapy yielded better outcomes. 22 Kuo et al showed improved survival with induction chemotherapy over adjuvant chemotherapy. 23 The heterogenous results of these studies underscore the need for future prospective trials on the efficacy of various treatment regimens for sinonasal malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…al. compared modalities for maxillary SCC, finding adjuvant and neoadjuvant multimodal therapy yielded better outcomes 20 . Kuo et al showed improved survival with induction chemotherapy over adjuvant chemotherapy 21 .…”
Section: Accepted Manuscriptmentioning
confidence: 98%